Soil temperature modifies effects of soil biota on plant growth. (20th September 2016) - Heinze, Johannes; Gensch, Sabine; Weber, Ewald; Joshi, Jasmin
Abstract: Aims: Plants directly and indirectly interact with many abiotic and biotic soil components. Research so far mostly focused on direct, individual abiotic or biotic effects on plant growth, but only few studies tested the indirect effects of abiotic soil factors on plant growth. Therefore, we investigated how abiotic soil conditions affect plant performance, via changes induced by soil biota. Methods: In a full-factorial experiment, we grew the widespread grass Dactylis glomerata either with or without soil biota and investigated the impact of soil temperature, fertility and moisture on the soil biota effects on plant growth. We measured biomass production, root traits and colonization by arbuscular mycorrhizal fungi as well as microbial respiration. Important Findings: We found significant interaction effects between abiotic soil conditions and soil biota on plant growth for fertility, but especially for soil temperature, as an increase of 10°C significantly changed the soil biota effects on plant growth from positive to neutral. However, if tested individually, an increase in soil temperature and fertility per se positively affected plant biomass production, whereas soil biota per se did not affect overall plant growth, but both influenced root architecture. By affecting soil microbial activity and root architecture, soil temperature might influence both mutualistic and pathogenic interactions between plants and soil biota. Such soil temperature effects should be considered in soil feedback studies to ensure greater transferability of results from artificial and experimental conditions to natural environmental conditions.